2020
DOI: 10.3389/fendo.2020.595109
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases the Severity and Mortality of Influenza and COVID-19: A Systematic Review and Meta-Analysis

Abstract: Since December 2019, COVID-19 has aroused global attention. Studies show the link between obesity and severe outcome of influenza and COVID-19. Thus, we aimed to compare the impacts of obesity on the severity and mortality of influenza and COVID-19 by performing a meta-analysis. A systematic search was performed in MEDLINE, EMASE, ClinicalTrials.gov, and Web of Science from January 2009 to July 2020. The protocol was registered onto PROSPERO (CRD42020201461). After selection, 46 studies were included in this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 69 publications
6
86
0
5
Order By: Relevance
“…The results of our study are in line with previous reports linking obesity and individual components of metabolic health with poor COVID-19 outcomes and death (1,5,7,10,12,18,37). In particular, the fact that waist circumference was related to COVID-19 mortality is consistent with a study showing that visceral adipose tissue is significantly related to the risk of admission to an intensive care unit in COVID-19 patients (38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are in line with previous reports linking obesity and individual components of metabolic health with poor COVID-19 outcomes and death (1,5,7,10,12,18,37). In particular, the fact that waist circumference was related to COVID-19 mortality is consistent with a study showing that visceral adipose tissue is significantly related to the risk of admission to an intensive care unit in COVID-19 patients (38).…”
Section: Discussionsupporting
confidence: 92%
“…Since the beginning of the COVID-19 pandemic, mounting evidence supports an association between obesity and poor outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The association holds for both obesity and obesityassociated metabolic healthhypertension, diabetes, dyslipidemia, and systemic inflammation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Poor quality diets are associated with progressively increasing weight gain, which can often lead to increased risk of central obesity and metabolic syndrome that can trigger a cascade of chronic disease risk factors, such as dyslipidemia, elevated blood glucose, hypertension, insulin resistance, increased systemic inflammation, and colonic microbiota dysfunction [106]. Obesity can also exacerbate severe adverse outcomes of influenza or COVID-19, associated with: (1) excessive abdominal fat, which pushes up on the diaphragm, causing the large muscle laying below the chest to restrict lung expansion and airflow, interfering with the delivery of oxygenated blood to the lower lung lobes, (2) increased risk for blood clotting, (3) weakened immune function because fat cells infiltrate immune organs such as the spleen, bone marrow, and thymus, making them less effective, and (4) elevated chronic, systemic low-grade inflammation, as fat cells are a major source of inflammation cytokines [107][108][109].…”
Section: Overviewmentioning
confidence: 99%
“…In the context of the COVID-19 outbreak, clinical severity may be partially attributable to the underlying myocardial abnormalities, metabolic disorders, and pre-existing cardiovascular disorders in obese patients. A subset of meta-analyses have recently been published, underscoring the association between obesity and critical illness in terms of the need for ICU admission or invasive mechanical ventilation and mortality from COVID-19 [ 46 49 ]. In the meta-analysis by Yang et al [ 47 ], obesity was associated with COVID-19 severity (OR 2.31; 95% CI, 1.3–4.12).…”
Section: Heart Health In the Context Of Covid-19 And Obesitymentioning
confidence: 99%
“…The association between obesity and severity is particularly relevant in younger obese COVID-19 patients (OR 3.3) [ 48 ]. Zhao et al [ 49 ] reported an OR of 2.07 (95% CI 1.53–2.81) between obesity and severe outcomes of COVID-19. Finally, obesity was found to be a risk factor for COVID-19 severity independent of cardiovascular disorders and diabetes [ 50 ].…”
Section: Heart Health In the Context Of Covid-19 And Obesitymentioning
confidence: 99%